Fetal hemoglobin altering effects of KLF1, BCL11A rs11886868 and XmnI-HBG2 on transfusion dependent beta thalassemia patients: Preeliminary study (Annals of Medical Research, 2023)
Aim: High fetal hemoglobin value is one of the quantitative trait in beta thalassemia and may effect transfusion dependency status of beta thalassemia cases. There are population-based differences about known genetic modifiers of different fetal hemoglobin values. We aimed to find if high fetal hemoglobin value are caused by XmnI-HBG2 polymorphism, rs11886868 of BCL11A or KLF1 whole gene mutations.Materials and Methods: Genotyping procedure of thirty well re-defined and characterized transfusion dependent beta thalassemia patients was conducted via either sanger sequencing or and PCR-RFLP. Statistical analysis of groups and multiple logistic regression analysis of related genotypes were performed.Results: We found strong correlations between transfusion dependency and fetal hemoglobin levels (PA) homozygous mutation was found to be predominant in HBB gene. Lower fetal hemoglobin levels were seen in IVS.I.110 (G>A) homozygous group (P0.05).Conclusion: This is the first research report from Turkey in terms of 3 different modifiers were  analyzed and evaluated. Since some cases have more than one variations in these three modifiers, involving higher sample size may overcome this challenge. Other genomic alterations rather than XmnI-HBG2, variations of BCL11A rs11886868 and mutation profile of KLF1 gene, which could decrease or abolish the effect of gamma globin repressors, may have more direct role with high fetal hemoglobin levels in patients with transfusion dependent beta thalassemia in Turkey.